(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Software Development Lifecycle plays a pivotal role in developing large-scale applications with numerous features by a large team of people in a fixed timeline. There are a variety of software development models available. One such popular model is called the Agile software development model. This is a popular framework used by a large number of companies today and has proven successful in developing small-scale to large-scale applications. In this paper, we gather the results of developing an application named course review portal that can be used to gain insights on courses available in universities. This will be beneficial for both the institution and the students in providing better elective choices and choosing the optimum choice respectively. The entire application runs client-side and communicates with a cloud database to fetch data. Continuous Integration and deployment are performed with Gitlab’s CI/CD tools. We further discuss the use of Scrum framework of agile methodology and present the effectiveness of the framework used and the novelty of the application built.